Follicle-stimulating hormone-dependent phosphorylation of vimentin in cultures of rat Sertoli cells. - Spruill, W A (1983)
Endogenous protein phosphorylation was investigated in cultured rat Sertoli cells after treatment with follicle-stimulating hormone (FSH) and pharmacological agents that activate cAMP-dependent protein kinases. In intact Sertoli cells, both phosphorylation and dephosphorylation of proteins occurred in response to treatment with these agents. Studies using cell-free preparations suggest that four phosphoproteins phosphorylated by cAMP or the catalytic subunit of cAMP-dependent protein kinase were also phosphorylated in a FSH-dependent manner in intact cells. These data suggest that FSH-dependent phosphorylation in Sertoli cells occurs through activation of a cAMP-dependent protein kinase. A FSH-dependent phosphoprotein with a molecular weight of 58,000 was identified as the intermediate filament protein vimentin, based on its migration in two-dimensional gels and its peptide map. The cellular distribution of vimentin was monitored by immunofluorescence in Sertoli cells after treatment with FSH. Results of this study support a role for intermediate filaments in FSH-dependent events in Sertoli cells.